Designing Ray-Pointing using Real hand and Touch-based in Handheld Augmented Reality for Object Selection (International Journal of Innovative Computing, 2021)
Augmented Reality (AR) have been widely explored worldwide for their potential as a technology that enhances information representation. As technology progresses, smartphones (handheld devices) now have sophisticated processors and cameras for capturing static photographs and video, as well as a variety of sensors for tracking the user's position, orientation, and motion. Hence, this paper would discuss a finger-ray pointing technique in real-time for interaction in handheld AR and comparing the technique with the conventional technique in handheld, touch-screen interaction. The aim of this paper is to explore the ray pointing interaction in handheld AR for 3D object selection. Previous works in handheld AR and also covers Mixed Reality (MR) have been recapped.
Keywords: 3D object selection, handheld, gesture, manipulation, interaction, raycasting, augmented reality, mixed reality